Reconsidering the origins of isotopic variations in Ocean Island Basalts: Insights from fine-scale study of Sao Jorge Island, Azores archipelago - Millet, Marc-Alban; Doucelance, Régis; Baker, Joel A.; Schiano, Pierre (Chemical Geology, 2009)
International audience